Considerations concerning the power loss in a gear system. Issue 1 (1st October 2022) - Ilieş, A; Bucur, M; Cananau, S; Mirica, R F; Gabroveanu, S
Abstract : The goal of the research is to assess the power losses in a gearbox with helical gears. In addition, the effects of each component of the total power loss in a gear transmission system are investigated. The study shows the important influence of the gear meshing power loss and discuss some aspects concerning the calculus formula. Also, the coefficient of friction is computed and the efficiency of the gear meshing system and the bearing rolling pair. Results are compared to a numerical results obtained by other researchers.